Peran GnRH agonis - Suparman, Erna; Suparman, Eddy (UNIVERSITAS SAM RATULANGI, 2016)
Abstract: Gonadotropin Releasing Hormone (GnRH) agonists have a higher biological potential than endogenous GnRH. Administration of a GnRH agonist triggers FSH and LH secretion from the pituitary (flare-up effect), however, after several days pituitary sensitivity continues to decrease which causes decreases of LH, FSH, estrogen, and progesterone (down-regulation). Preoperative administration of GnRH agonists is recommended in uterine fibroid with severe anemia to reduce blood loss before, during, and after surgery. Due to shrinking of fibroid, laparoscopy or laparotomy with Pfannenstiel incision can be performed. Moreover, myomectomy will not require extensive incision, damaged myometrium and adhesion are minimum, therefore, those conditions will increase the success of fertility; facilitate the removal of submucosal fibroid with histeroscopy; and enable the vaginal hysterectomy more easily. In patients with polycystic ovarial syndrome, GnRH agonists will suppress the high levels of LH and testosterone. GnRH agonists halt the growth and reduce the size of an endometriosis, therefore, they can be used in patients with precocious puberty and premenstrual syndrome. The combination of exogenous gonadotropin plus a GnRH agonist used in vitro fertilization is associated with increased pregnancy rate as compared with the use of gonadotropins without a GnRH agonist. The administration of GnRH agonists trigger hypoestrogen that causes osteoporosis and other complaints such as hot flushes, vaginal dryness, headache, and sleep disturbance. GnRH agonists can be combined with low-dose estrogen and progestin (add-back therapy) to reduce these side effects. Addback provision of therapy is started 12 weeks after administration of GnRH agonists.Keywords: GnRH agonist, exogenous gonadotropinAbstrak: GnRH (Gonadotropin Releasing Hormone) agonis memiliki potensi biologis yang lebih tinggi daripada GnRH endogen. Permulaan pemberian GnRH agonis memicu pengeluaran FSH dan LH dari hipofisis (flare-up effect). Setelah beberapa hari sensitivitas hipofisis terhadap rangsangan GnRH agonis terus berkurang yang menyebabkan penurunan LH, FSH, estrogen, dan progesteron (down regulation). Pemberian GnRH agonis preoperatif dianjurkan pada mioma uteri dengan anemia berat untuk mengurangi kehilangan darah sebelum, selama dan setelah operasi. Dengan mengecilnya mioma maka dapat dilakukan tindakan laparoskopi atau laparatomi dengan insisi Pfannenstiel, juga saat miomektomi tidak diperlukan insisi luas, kerusakan miometrium dan perlekatan menjadi minimal sehingga akan meningkatkan keberhasilan fertilitas; mempermudah pengangkatan mioma submukosum dengan histeroskopi; dan mempermudah melakukan vaginal histerektomi. GnRH agonis pada pasien sindroma ovarium polikistik akan menekan tingginya kadar LH dan produksi testosteron. GnRH agonis menghentikan pertumbuhan dan mengurangi ukuran endometriosis, selain itu GnRH agonis dapat digunakan pada pasien dengan pubertas prekok dan sindroma premenstrual. Pada fertilisasi in vitro penggunaan kombinasi gonadotropin eksogen ditambah GnRH agonis berhubungan dengan peningkatan keberhasilan kehamilan dibandingkan dengan penggunaan gonadotropin tanpa GnRH agonis. Pemberian GnRH agonis memicu keadaan hipoestrogen yang menyebabkan osteoporosis dan keluhan lain seperti hot flushes, vagina yang kering, sakit kepala, dan gangguan tidur. GnRH agonis dapat dikombinasi dengan estrogen dosis rendah dan progestin (add-back therapy) untuk mengurangi efek samping tersebut. Pemberian addback therapy ini dimulai 12 minggu setelah pemberian GnRH agonis.Kata kunci: GnRH agonis, gonadotropin eksogen